Edukacja emocjonalna a rozwój emocjonalny dziecka - Kubiak, Hanna; Kubiak-Frątczak, Aleksandra (Studia Edukacyjne, 2022)
In recent years, the need to consciously care for the emotional development of children has been increasingly recognized in the social space. The concepts of emotional intelligence (Goleman, 2007) or emotional competence (Saarni, 1988, pp. 115-82) reflect the interest in this particular sphere of development. This type of intelligence includes the ability to understand one’s own and others’ emotions, which is the source of competences related to reading emotions, being aware of and “managing” them. They are to enable the achievement of a wide range of goals: interpersonal, professional and related to selfdevelopment. Realizing this potential largely depends on the course of the emotional development process. The aim of this article is to outline the framework for the emotional development of a child, to search for ways to strengthen protective factors and to indicate methods of supporting children and adults – parents, teachers, educators, psychologists, and doctors.